CEO Turnover–Performance Sensitivity in Private Firms - Gao, Huasheng; Harford, Jarrad; Li, Kai (Journal of Financial and Quantitative Analysis, 2017)
We compare chief executive officer (CEO) turnover in public and large private firms. Public firms have higher turnover rates and exhibit greater turnover–performance sensitivity (TPS) than private firms. When we control for pre-turnover performance, performance improvements are greater for private firms than for public firms. We investigate whether these differences are due to differences in quality of accounting information, the CEO candidate pool, CEO power, board structure, ownership structure, investor horizon, or certain unobservable differences between public and private firms. One factor contributing to public firms’ higher turnover rates and greater TPS appears to be investor myopia.